Melemahnya Budaya Jamu Cekok Di Kelurahan Pare - Siti Zulaikha; Nur Hadi; Joan Hesti Gita Purwasih (Universitas Andalas, 2021)
Jamu is a traditional medicine that has been widely known by the Indonesian people. One kind of herbal medicine is now rarely used, namely herbal suppression. The term cekok comes from the Javanese language which means to drink by force. The purpose of this study is to describe how the weakening of the herbal medicine culture in Pare Village. Research using ethnographic qualitative methods with interview and observation techniques. The results of this study indicate that the community sees the existence of herbal suppressants. However, there are not as many devotees as before. As an analytical technique, the author uses an anthropological perspective on medical health behavior according to Notoatmodjo to explain the data found. Data analysis used is the data used, data reduction, and data presentation in the form of descriptions. This study shows that the weakening of the herbal medicine culture, including the number of more modern dietary supplements for children; parents who do not have the heart to do the prostitution process; and the knowledge of parents about the recipe for making the herbal-punching herb